2022
DOI: 10.1049/hve2.12290
|View full text |Cite
|
Sign up to set email alerts
|

Axial and radial electromagnetic‐vibration characteristics of converter transformer windings under current harmonics

Abstract: The winding current harmonic content of converter transformer in operation is rich. However, affected by harmonics, the radial vibration characteristics are quite different from the power transformer, structural loosening and deformation caused by winding vibration are more prominent. Therefore, in view of the influence of current harmonics on axial and radial vibrations, this study builds a 3D winding electromagnetic vibration finite element simulation model, analyses the components and contents of current ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…There is a linear positive correlation between the longitudinal leakage magnetic flux density of the main air channel and the harmonic current content. For every 1% increase in the harmonic current content, the longitudinal magnetic leakage density in the middle of the main magnetic leakage channel increases by 0.00249 T, and the longitudinal magnetic leakage density at the end increases by 0.00124 T as shown in formulas (11) and (12). The transverse magnetic leakage density is the highest at both ends of the main magnetic leakage channel, and the transverse magnetic leakage directions at the upper and lower ends are opposite.…”
Section: Magnetic Flux Density Distribution and Loss Distribution Und...mentioning
confidence: 86%
See 2 more Smart Citations
“…There is a linear positive correlation between the longitudinal leakage magnetic flux density of the main air channel and the harmonic current content. For every 1% increase in the harmonic current content, the longitudinal magnetic leakage density in the middle of the main magnetic leakage channel increases by 0.00249 T, and the longitudinal magnetic leakage density at the end increases by 0.00124 T as shown in formulas (11) and (12). The transverse magnetic leakage density is the highest at both ends of the main magnetic leakage channel, and the transverse magnetic leakage directions at the upper and lower ends are opposite.…”
Section: Magnetic Flux Density Distribution and Loss Distribution Und...mentioning
confidence: 86%
“…Jiang Peiyu et al. studied the electromagnetic distribution characteristics of converter transformers under harmonic current [12]. Zhang, L. et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacement field of the winding-block structure has a strong coupling relationship with the electromagnetic field under electromagnetic force excitation, and the axial natural vibration frequency of large capacity transformers is usually between 50 and 100 Hz. Therefore, using the dynamic method (DM) to calculate the axial short-circuit force is able to accurately reflect the actual situation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the pad would show strong nonlinear characteristics under the state of stress, the elastic coefficient would increase sharply with the increase of pressure, the stiffness would harden obviously with the increase of stress, and the content of high-frequency components in the vibration signal would increase. In Literature [11] and Literature [12], a threedimensional finite element model was established, and the mechanical properties of the elastic element in the winding structure-the insulating pad were tested under different preload, temperature, and aging degrees. The results show that decreasing the preload, increasing the temperature, or aging time can decrease Young's modulus of the pad.…”
Section: Introductionmentioning
confidence: 99%